- #1

- 9

- 0

Below is the address of an attempted proof of FLT that I have not been able to find a flaw in. It works by increasing x, y, and z by a common integer factor so that, if x^p +y^p = z^p, with x + y = a^p and z - y = b^p, then (z/a) = (x/b)^((1 + 1/(p-1)) (mod g), with g a prime factor of y that is coprime to z - x. The total argument is 23 lines long.

http://groups.google.com/group/fermats-last-theorem-flt-2008

http://groups.google.com/group/fermats-last-theorem-flt-2008

Last edited: